International law and transboundary dams: lessons learned from the Binational Entity ITAIPU (Brazil and Paraguay) - Gwynn, Maria A. (Frontiers in Climate, 2023)
The international river Paraná flows through Brazil, Paraguay and Argentina, and holds two major binational dams: the upstream ITAIPU dam (Brazil-Paraguay) and the downstream Yacyreta dam (Argentina-Paraguay). In the past years, the South American region was strongly affected by adverse environmental challenges exacerbated by climate change, like wildfires and severe droughts, which in turn drastically affected the water flow of the Paraná river, a river used for multiple purposes, inter alia the production of energy. The hydropower obtained from ITAIPU is one of the main sources of energy for Paraguay and the Southern part of Brazil. At the same time, the downstream parts of the river is used for navigation purposes, which is crucial for land-locked Paraguay to export its agricultural products, and for water consumption, as is the case for Argentina. The present case study will show how in spite of these challenges, South America has been an successful example of transboundary water cooperation, especially by using the international water law guidelines aimed at achieving reasonable and equitable utilization of an international river.